Approximate Analytic Solution for the KdV and Burger Equations with the Homotopy Analysis Method - Mojtaba Nazari; Faisal Salah; Zainal Abdul Aziz; Merbakhsh Nilashi (Journal of Applied Mathematics)
The homotopy analysis method (HAM) is applied to obtain the approximate analytic solution of the Korteweg-de Vries (KdV) and Burgers equations. The homotopy analysis method (HAM) is an analytic technique which provides us with a new way to obtain series solutions of such nonlinear problems. HAM contains the auxiliary parameter ħ, which provides us with a straightforward way to adjust and control the convergence region of the series solution. The resulted HAM solution at 8th-order and 14th-order approximation is then compared with that of the exact soliton solutions of KdV and Burgers equations, respectively, and shown to be in excellent agreement.